Assessing the determinants of agricultural commercialization and challenges confronting cassava farmers in Oyo State, Nigeria - Olutosin Ademola Otekunrin; Idris Akanbi Ayinde; Rahman Akintayo Sanusi; Oluwaseun Aramide Otekunrin (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
This study assesses the agricultural commercialization levels, determinants, and challenges confronting smallholder cassava farmers in Oyo State, Nigeria. This study was conducted in Oyo State, Nigeria using cross-sectional data from 211 smallholder cassava farmers and employing multi-stage sampling procedures. Descriptive statistics, Crop Commercialization Index (CCI), and Ordered Logit Model (OLM) were used to analyze the data collected. The results revealed that 83.9% of the cassava farmers participated in the commercialization of their cassava roots while the remaining farmers were non-participants. The greatest challenge faced by the cassava farmers in the study area was the incessant attacks by the Fulani herdsmen (destroying growing cassava on the farm) while other challenges included cassava cyclical gluts and poor access road. Moreover, OLM revealed that age, farm size, cassava marketing experience and distance to market had significant influence on commercialization levels of cassava farmers. However, in order to enhance increased commercialization levels of cassava farmers and peaceful coexistence in the study area, policies and intervention programmes that will facilitate rural infrastructure development and proffer lasting solution to the farmers-herders crisis should be given upmost priority.JEL Classification D13; M31; Q19